Dynamic monitoring of functional status in athletes performing physical loads in vertical and horizontal planes with equivalent energy supply for muscle training - Yevhen Mykhaliuk; Yehor Horokhovskyi; Anatolii Bosenko; Mykhailo Khoroshukha; Oksana Pavliuk (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose. To dynamically monitor the functional state of athletes undergoing physical loads in vertical and horizontal planes with similar energy demands during the training cycle.